Creación de una revista Informativa-Turística para el cantón Sigchos. - Calvopiña Grandes, Erika Paola (2018)
The project is based on the research lines of the career and focuses on a diagnosis to establish the degree of interest for domestic and foreign tourists to know tourist places of the Sigchos canton Cotopaxi province. A qualitative approach was applied, because it covered the collection of data through the holding of discussion groups; a sample of 30 national and foreign tourists visiting the canton and 30 residents of the sector was chosen, and a scheme of categories with different codes that identify the degree of interest in knowing the tourist places of the province with different categories in the which was a comparison between the participants Based on the information collected, it is proposed to design a tourist information magazine of the Sigchos canton, based on the journalistic principles of truthfulness and objectivity, with verifiable information, attached to reality, which will serve as an informative supplement, for which informative material will be collected. the canton, through a visit to libraries where texts from the web containing cultural data of the canton will be collected, a field research will be carried out, where some information about the canton will be obtained, going to the place of the study and there making observations, interviews that they provide us with enough material to be included in the proposed magazine. The collected material will be studied, to separate the appropriate information for the magazine, all with the purpose of being received by the public and used in tourist activities. Among the direct and indirect beneficiaries we have 23,236 people. It was concluded that tourists are interested in knowing the different tourist places that the Sigchos canton offers, and the best way to access them is with a guide that allows them to venture to discover new places where they can enjoy, relax and connect with nature leaving aside daily stress. For what stood out the tourist and cultural potential that it has, the canton Sigchos, Province of Cotopaxi, as much in its material and immaterial wealth, same that has not been valued in its real dimension and for that reason, by means of this effort, It seeks to rescue it in all its aspects, so that it can be disseminated nationally and even internationally.